2015
DOI: 10.1016/j.bpj.2015.04.037
|View full text |Cite
|
Sign up to set email alerts
|

Experiments on Hemoglobin in Single Crystals and Silica Gels Distinguish among Allosteric Models

Abstract: Trapping quaternary structures of hemoglobin in single crystals or by encapsulation in silica gels has provided a demanding set of data to test statistical mechanical models of allostery. In this work, we compare the results of those experiments with predictions of the four major allosteric models for hemoglobin: the quaternary two-state model of Monod, Wyman, and Changeux; the tertiary two-state model of Henry et al., which is the simplest extension of the Monod-Wyman-Changeux model to include pre-equilibria … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

6
44
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(50 citation statements)
references
References 64 publications
6
44
0
Order By: Relevance
“…Moreover, the sickle fiber binds oxygen with an affinity that is very similar to the T quaternary structure in the crystal. 69,70 These results are consistent with structural analysis, which shows that the arrangement of the subunits in the R structure produces many steric clashes 71 that preclude incorporation into the T-containing fiber.…”
Section: Increase Oxygen Affinitysupporting
confidence: 79%
“…Moreover, the sickle fiber binds oxygen with an affinity that is very similar to the T quaternary structure in the crystal. 69,70 These results are consistent with structural analysis, which shows that the arrangement of the subunits in the R structure produces many steric clashes 71 that preclude incorporation into the T-containing fiber.…”
Section: Increase Oxygen Affinitysupporting
confidence: 79%
“…Over and above presenting their data, Henry et al (9) discuss the TTS model by comparison with previous articles, and particularly the statistical mechanical description of Perutz's stereochemical mechanism published by Szabo and Karplus (10).…”
mentioning
confidence: 96%
“…Perutz et al (6) had discovered that deoxy human Hb, crystallized from polyethylene glycol at low pH, maintains the salt bridges intact even upon ligand saturation. Accurate oxygen binding curves of these crystals obtained by microspectrophotometry (Henry et al (9) and references therein) showed that 1) the saturation curve is noncooperative (Hill's coefficient n ¼ 1); and 2) the oxygen affinity is very low and independent of pH, BPG, and other effectors. These findings are consistent with predictions of the MWC model whereby stabilization of the T state is associated to low affinity, and inconsistent with the Koshland, Nemethy, and Filmer-induced fit mechanism.…”
mentioning
confidence: 98%
See 2 more Smart Citations